2015
DOI: 10.1186/s12915-015-0186-5
|View full text |Cite
|
Sign up to set email alerts
|

Systems-level organization of yeast methylotrophic lifestyle

Abstract: BackgroundSome yeasts have evolved a methylotrophic lifestyle enabling them to utilize the single carbon compound methanol as a carbon and energy source. Among them, Pichia pastoris (syn. Komagataella sp.) is frequently used for the production of heterologous proteins and also serves as a model organism for organelle research. Our current knowledge of methylotrophic lifestyle mainly derives from sophisticated biochemical studies which identified many key methanol utilization enzymes such as alcohol oxidase and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
158
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(169 citation statements)
references
References 76 publications
8
158
2
1
Order By: Relevance
“…The observed changes in lipid droplet (LDs) morphology might be indicative of the dramatic effects that the scarcity of nutrients/energy has on the regulation of lipid metabolism (Rußmayer et al, 2015). In yeast cells, LDs are particularly dynamic throughout the growth phase and depending on the nutritional status of the cell (Kurat et al, 2006;Bozaquel-Morais et al, 2010).…”
Section: Lipid Droplets Change Their Morphology Upon Energy Depletionmentioning
confidence: 99%
“…The observed changes in lipid droplet (LDs) morphology might be indicative of the dramatic effects that the scarcity of nutrients/energy has on the regulation of lipid metabolism (Rußmayer et al, 2015). In yeast cells, LDs are particularly dynamic throughout the growth phase and depending on the nutritional status of the cell (Kurat et al, 2006;Bozaquel-Morais et al, 2010).…”
Section: Lipid Droplets Change Their Morphology Upon Energy Depletionmentioning
confidence: 99%
“…The lipid composition of this yeast has also been studied with regard to a carbon source effect [38]. However, such fundamental studies were performed exclusively using wild type strains.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, as our previous transcriptomic study revealed a high impact of the overexpression of ROL on the peroxisomal pentose phosphate regeneration pathway (PPP) and peroxisome biogenesis in ROL multicopy strains (Cámara et al, 2017), the mRNA levels of fructose 1,6-bisphosphate aldolase (FBA1-2) and peroxine 6 (PEX6) were selected as markers of these pathways. In the case of FBA1-2, an increase of 40% and 36% was detected for 4C 6 -2MXR1* and 4C-MIT1 strains, respectively, supporting the role of the peroxisomal PPP in methanol assimilation (Rußmayer et al, 2015).…”
Section: Chemostat Cultures Reveal a Shift In The Csource Consumptimentioning
confidence: 56%
“…In the case of FBA1-2, an increase of 40% and 36% was detected for 4C 6 -2MXR1* and 4C-MIT1 strains, respectively, supporting the role of the peroxisomal PPP in methanol assimilation (Rußmayer et al, 2015). In the case of FBA1-2, an increase of 40% and 36% was detected for 4C 6 -2MXR1* and 4C-MIT1 strains, respectively, supporting the role of the peroxisomal PPP in methanol assimilation (Rußmayer et al, 2015).…”
Section: Chemostat Cultures Reveal a Shift In The Csource Consumptimentioning
confidence: 68%